Neuroprotective effects of 1‐O‐hexyl‐2, 3, 5‐trimethylhydroquinone on ischaemia/reperfusion‐induced neuronal injury by activating the Nrf2/HO‐1 pathway. Issue 18 (17th July 2020) - Tang, Chaoliang; Hu, Yida; Lyu, Haiyan; Gao, Jie; Jiang, Jiazhen; Qin, Xiude; Wu, Yuanbo; Wang, Jiawu; Chai, Xiaoqing
Abstract: 1‐O‐Hexyl‐2, 3, 5‐trimethylhydroquinone (HTHQ), a lipophilic phenolic agent, has an antioxidant activity and reactive oxygen species (ROS) scavenging property. However, the role of HTHQ on cerebral ischaemic/reperfusion (I/R) injury and the underlying mechanisms remain poorly understood. In the present study, we demonstrated that HTHQ treatment ameliorated cerebral I/R injury in vivo, as demonstrated by the decreased infarct volume ration, neurological deficits, oxidative stress and neuronal apoptosis. HTHQ treatment increased the levels of nuclear factor erythroid 2–related factor 2 (Nrf2) and its downstream antioxidant protein, haeme oxygenase‐1 (HO‐1). In addition, HTHQ treatment decreases oxidative stress and neuronal apoptosis of PC12 cells following hypoxia and reperfusion (H/R) in vitro. Moreover, we provided evidence that PC12 cells were more vulnerable to H/R‐induced oxidative stress after si‐Nrf2 transfection, and the HTHQ‐mediated protection was lost in PC12 cells transfected with siNrf2. In conclusion, these results suggested that HTHQ possesses neuroprotective effects against oxidative stress and apoptosis after cerebral I/R injury via activation of the Nrf2/HO‐1 pathway.